Penerapan Metode Tahfidz Dan Takrir Dalam Meningkatkan Kualitas Hafalan Santri Madrasah Quran Asrama Al-Umami - Roviatun Nafiah; Marlina; Romdloni (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Nurul Huda, 2022)
There are many ways in the process of maintaining the purity of the Qur'an, one of which is memorizing the Qur'an. In the memorization process, of course, it is not easy, by reading it immediately memorized, but there are several methods that are also used to simplify and speed up the memorization process. This study aims to determine: 1) the application of the tahfidz and takrir methods, 2) the quality of memorization of the students of the Madrasah Qur'an in the Al-Umami Dormitory of the Nurul Huda Islamic Boarding School, Sukaraja. The research approach used is qualitative with descriptive research type. The results showed that the application of the tahfidz and takrir methods in improving the memorization quality of the students of Madrasah Qur'an Al-Umami Dormitory was very effective. Meanwhile, efforts to improve the quality of memorization have also been systematically arranged.